28 Are we measuring what we think we are measuring? Qualitative research exploring the role of the 0–10 pain score within the adult emergency department. Issue 12 (23rd November 2017) - Sampson, Fiona; O'cathain, Alicia; Goodacre, Steve
Abstract : Objectives and background: The assessment of pain in the emergency department (ED) is difficult but important for appropriate management of pain. Guidelines for the management of acute pain in the ED worldwide advocate using numeric rating scales such as the 0–10 pain score as tools to ensure consistency of documenting patient's pain, and this is mandated at initial assessment in many EDs. Studies of interventions to improve pain management in the ED indicate that whilst the inclusion of mandatory pain scoring within interventions may improve documentation of pain, there was mixed evidence as to whether this resulted in improvements in provision of analgesia. As part of a wider study looking at barriers and enablers to pain management in the ED, we explored how pain scoring was used in the ED. Methods: Qualitative data were collected within 3 case study EDs in the UK. Data comprised 143 hours of non-participant observation, 37 ED staff interviews and 19 patient interviews. Data were analysed using thematic analysis. Results: Observation showed variation in how the pain score was documented between EDs. Some staff documented the score directly reported by the patient, whilst others documented a score they formulated using a combination of physiological signs, behavioural signs and presence of a 'known' painful condition. ED staff appeared to understand the score as an absolute measure used to guide analgesia requirements or triage categories rather than a relative measure used to document changes in pain levels. Even when documenting patient reported scores, they perceived patient reported scores to be inconsistent with their own assessment of the patients pain level, particularly where this could lead to patients being managed under a higher triage category or receiving stronger analgesia than ED staff considered appropriate. Staff documented pain scores that were appropriate for the treatment they planned to provide, rather than the scores reported by the patient, in particular when the pain score was used as a tool for auditing appropriate pain management. Conclusions: The pain score appeared to have parallel but misaligned roles: to assess patient pain and ED staff practice. ED staff faced conflict between the need to record pain to ensure accountability of pain management, and recording pain to reflect the patient's report. The role of the pain score needs to be reviewed in order for pain scoring to improve the patient experience of pain management in the ED.